Synthesis, crystal structure and remote allosteric binding properties of cone thiacalix[4]pseudocrown receptors bearing anthraquinone function and different arms. Issue 56 (17th July 2017) - Lv, Xue-Xin; Wang, Qian; Zhang, Li-Jing; Liu, Ling-Ling; Zhao, Mei; Guo, Dian-Shun
Abstract : Herein, three novel cone thiacalix[4]pseudocrown receptors1–3, bearing anthraquinone and triazole functions as well as different side arms, were successfully synthesized via a double click reaction as the key step. Abstract : Herein, three novel cone thiacalix[4]pseudocrown receptors1–3, bearing anthraquinone and triazole functions as well as different side arms, were successfully synthesized via a double click reaction as the key step. Their recognition properties have been fully evaluated using optical, electrochemical, and theoretical methods. Receptor1 features high selectivity for Pb 2+, whereas receptor2 can optically recognize Zn 2+ in the presence of Cd 2+ . This difference of binding specificity to metal ions may be ascribed to the remote tuning effect from the side arms connected to the lower rim of thiacalix[4]arene that realizes the accommodation of binding specificity. Moreover, the plausible coordination modes have been presented.